2014
DOI: 10.1080/13657305.2014.903310
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Temperature in Farmed Salmon Growth: Regional Growth Functions for Norwegian Farmed Salmon

Abstract: A reliable growth function is a vital part of deriving the optimal harvesting strategy and production plan for any aquaculture operation. The range of environmental and biological conditions along the Norwegian coast suggests that the growth of farmed salmon will differ from one region to another. We estimate an aggregated regional growth function for three different regions in Norway using monthly data from 2005 to 2011. There is currently some variation for the grow-out period, and Atlantic salmon is raised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…In Chile, the life cycle is slightly shorter as the sea water temperatures are closer to the optimum temperature for Atlantic salmon (Marine Harvest, 2015). In Norway, with its extensive, stretched coastline, it has been shown that salmon grows faster to marketable size in the South than in the North, yet this may change upon further warming of the sea over time as caused by climate change (Thyholdt, 2014;Harvest, 2016). Also throughout the year and between years, seawater temperature and consequently production vary, with Norwegian salmon showing the greatest part of the annual feed consumption (67%) and growth (68%) in the months of June-November, coinciding with the annual fluctuation temperature, peaking in August and decreasing from September onwards .…”
Section: Smoltificationmentioning
confidence: 99%
See 3 more Smart Citations
“…In Chile, the life cycle is slightly shorter as the sea water temperatures are closer to the optimum temperature for Atlantic salmon (Marine Harvest, 2015). In Norway, with its extensive, stretched coastline, it has been shown that salmon grows faster to marketable size in the South than in the North, yet this may change upon further warming of the sea over time as caused by climate change (Thyholdt, 2014;Harvest, 2016). Also throughout the year and between years, seawater temperature and consequently production vary, with Norwegian salmon showing the greatest part of the annual feed consumption (67%) and growth (68%) in the months of June-November, coinciding with the annual fluctuation temperature, peaking in August and decreasing from September onwards .…”
Section: Smoltificationmentioning
confidence: 99%
“…Also throughout the year and between years, seawater temperature and consequently production vary, with Norwegian salmon showing the greatest part of the annual feed consumption (67%) and growth (68%) in the months of June-November, coinciding with the annual fluctuation temperature, peaking in August and decreasing from September onwards . Another important factor besides temperature is daylight, which depends on the season and latitude, whilst currently artificial light is also applied as compensation for lack of natural light during winter and spring, so as to increase productivity (Thyholdt, 2014;Harvest, 2016).…”
Section: Smoltificationmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the steps to achieve the fishery‐CBA joint sustainability is to determine and use a reliable biological production function able to explain biomass dynamics during the production cycle with the purpose of optimizing feed regimes and harvest dates. These two elements are essential to design an optimal production plan to maximize profitability (Arnason, ; Hernández, Leon‐Santana, & Leon, ; Leung & El‐Gayar, ; Thyholdt, ; Tian, Leung, & Hochman, ).…”
Section: Introductionmentioning
confidence: 99%